Information Access Pattern by Faculty Members And Students In Electronic Environment: A Study on Manonmaniam Sundaranar University Constituent College, Sathankulam - Rukamani, Ratha; L.N. Umadevi, (International Journal of Psychosocial Rehabilitation, 2020)
This paper discuss on information access pattern by faculty members and Students in Electronic Environment: A Study on Manonmaniam Sundaranar University Constituent College, Sathankulam. Totally 1231 respondents were participated in the present study, amongst male respondents are 423, female respondents are 808, moreover Assistant Professor are participated 45, Undergraduate Students are participated 98, and Postgraduate Students are participated 1088 respondents. The present study reveals that amongst 1231 respondents, 39.2 per cent are visited library daily, 27.7 per cent respondents are visited Once a week, 18.4 per cent respondents are visited Occasionally, 8.9 per cent respondents are visited monthly once, 5.8 per cent respondents are visited fortnightly once. Respondents access internet indicates that, 62.7 per cent of respondents are access internet at Institution and Home, followed by access at Institution, Home and Cyber café, Cyber cafe and Home, Institutions only, 4.5 per cent are access at Institution and Cyber café. Respondents’ preferences to access electronic resources, amongst 291 respondents are preferences E-newspapers, followed by E journals, Audio video materials, E-books, E-thesis and dissertations. The Satisfaction level of access e resources by the respondents, among the respondents 17.6 percent of them fully satisfied with access e resources, followed by 43.3 percent are Satisfied, and 39.1 percent of them are Dissatisfied with access e-resources.